The rise of Western power : a comparative history of Western civilization - Daly, Jonathan W. (London : Bloomsbury Academic, 2021)
"In this second edition of The Rise of Western Power, Jonathan Daly retains the broad sweep of his introduction to the history of Western civilization as well as introducing new material into every chapter, enhancing the book's global coverage and engaging with the latest historical debates. The West's history is one of extraordinary success: no other region, empire, culture, or civilization has left so powerful a mark upon the world. Daly charts the West's achievements-representative government, the free enterprise system, modern science, and the rule of law-as well as its misdeeds: two World Wars, the Holocaust, imperialistic domination, and the Atlantic slave trade. Taking us through a series of revolutions, he explores the contributions of other cultures and civilizations to the West's emergence, weaving in historical, geographical, and cultural factors. The new edition also contains more material on themes such as the environment and gender, and additional coverage of India, China and the Islamic world. Daly's engaging narrative is accompanied by timelines, maps and further reading suggestions, along with a companion website featuring study questions, over 100 primary sources and 60 historical maps to enable further study."--
Prologue: Why the West? -- 1. Innovation in World Civilization -- 2. Medieval Transformations -- 3. Papal Revolution -- 4. Military Revolutions -- 5. Discovery of the World -- 6. Explosion of the Printed Word -- 7. The Reformation -- 8. Scientific Revolutions -- 9. Commercial Revolutions -- 10. Political Revolutions -- 11. Industrial Revolution -- 12. Technological Revolution -- 13. Crises of the West -- 14. Social Revolutions -- Conclusion: A New Type of Society -- Notes -- Annotated Bibliography -- Index.
Includes bibliographical references and index.
Also issued in print: Bloomsbury Academic, 2021. Digital resource published 2022.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on online resource; title from digital title page (viewed on July 03, 2022).
Keywords: Civilization, Western; European history; History: earliest times to present day; Electronic books